Outcomes of abdominal wall reconstruction in complex ventral hernia patients: a single institution based prospective study - Khanal, Bhawani; Kumar, Abhijeet; Panta, Ashok; Chhetri, Susmita Khadka; Regmi, Parbatraj; Sah, Vijay Pratap; Sah, Bikash Kumar; Lomanto, Davide; Gupta, Rakesh Kumar (Frontiers in Surgery, 2025)
IntroductionComplex ventral hernias, especially in patients with prior surgeries, large defects, or comorbidities, are associated with high rates of recurrence and complications such as infection, pain, and loss of abdominal domain. This study aims to contribute to developing standardised management strategies.MethodsA prospective study was conducted at BP Koirala Institute of Health Sciences over two years, involving 38 patients undergoing abdominal wall reconstruction for complex ventral hernias. Preoperative assessment included NCCT and selective use of botulinum toxin for optimisation. Surgical approaches were individualised. Data on demographics, hernia characteristics, surgical technique, operative time, complications, hospital stay, recurrence, and chronic pain were collected and analysed.ResultsOf 88 ventral hernia cases, 44 were complex; 38 underwent repair. Most were incisional hernias located at M2–M5, with a mean defect size of 7.1 ± 2.9 cm. Mean operative time was 154.8 ± 51.6 minutes. Complications included seroma (15.6%), SSI (15.6%), hematoma (5.3%), and enterotomy (5.3%). Average hospital stay was 2.8 ± 1.2 days; activity resumed in 7.5 ± 2.9 days. At 2-year follow-up, recurrence was seen in 5.2%.ConclusionTailored individualised planning is crucial in complex abdominal reconstruction due to patient and defect variability, making standard techniques impractical.